Frequency and predictors of acute ischaemic lesions on brain magnetic resonance imaging in young patients with a clinical diagnosis of transient ischaemic attack. (23rd April 2016) - Tanislav, C.; Grittner, U.; Fazekas, F.; Thijs, V.; Tatlisumak, T.; Huber, R.; von Sarnowski, B.; Putaala, J.; Schmidt, R.; Kropp, P.; Norrving, B.; Martus, P.; et al.
Abstract : Background and purpose: Acute lesions in patients with transient ischaemic attack (TIA) are important as they are associated with increased risk for recurrence. Characteristics associated with acute lesions in young TIA patients were therefore investigated. Methods: The sifap1 study prospectively recruited a multinational European cohort ( n = 5023) of patients aged 18–55 years with acute cerebrovascular event. The detection of acute ischaemic lesions was based on diffusion‐weighted imaging (DWI). The frequency of DWI lesions was assessed in 829 TIA patients who met the criteria of symptom duration <24 h and their association with demographic, clinical and imaging variables was analysed. Results: The median age was 46 years (interquartile range 40–51 years); 45% of the patients were female. In 121 patients (15%) ≥1 acute DWI lesion was detected. In 92 patients, DWI lesions were found in the anterior circulation, mostly located in cortical‐subcortical areas ( n = 63). Factors associated with DWI lesions in multiple regression analysis were left hemispheric presenting symptoms [odds ratio (OR) 1.92, 95% confidence interval (CI) 1.27−2.91], dysarthria (OR 2.17, 95% CI 1.38−3.43) and old brain infarctions on MRI (territories of the middle and posterior cerebral artery: OR 2.43, 95% CI 1.42−4.15; OR 2.41, 95% CI 1.02−5.69, respectively). Conclusions: In young patients with a clinical TIA 15% demonstrated acute DWI lesions on brain MRI, with an event pattern highly suggestive of an embolic origin. Except for the association with previous infarctions there was no clear clinical predictor for acute ischaemic lesions, which indicates the need to obtain MRI in young individuals with TIA. Abstract : Clickhere to view the accompanying paper in this issue.